Factors affecting employee loyalty among teachers at the private schools in Batu Pahat, Johor / Norismadatul Iqma Muhamad Zameri - Muhamad Zameri, Norismadatul Iqma (Faculty of Business and Management, 2019)
Many organizations nowadays have a huge risk on losing its valuable employees is the new phenomenon of current’s talent starved job market. Globalization takes place makes employees need to face restructuring, movement of organization, and downsizing. Due to this situation, it then changed the environment and culture inside the organization, reduces the trust of workforce and change employees commitment towards organizations. When this change becomes unavoidable, the loyalty of an employee and their motivation becomes significant challenges that must be faced by most organizations in the current business area. So, this project-paper aims to investigate the factors affecting employee loyalty among teacher at the private schools in Batu Pahat, Johor. The response rate in this study is 79.05%. The hypothesis then constructed and being tested with reliability analysis, descriptive analysis, Pearson Correlation analysis and multiple regression analysis. All three hypotheses developed are accepted. The finding in this study indicates that, the loyalty of teacher in private schools is influence by superior-subordinate relationship, career development an empowerment. There is significant correlation between the relationships of these three factors with employee loyalty. Career development is the most influential factor that makes teacher in private schools loyal towards their organization and employer. The implications and suggestion for future researcher are identified and proposed in the last chapter of this study.